Dietary natural products as a potential inhibitor towards advanced glycation end products and hyperglycemic complications: A phytotherapy approaches - Vijaykrishnaraj M. (Elsevier, 2021)
Natural products exist in various natural foods such as plants, herbs, fruits, and vegetables. Furthermore, marine life offers potential natural products with significant biological activity. The biochemical reaction is known as advanced glycation end products (AGEs) occurs in the human body. On the other hand, foods are capable of a wide range of processing conditions resulting in the generation of exogenous AGEs adducts. Protein glycation and the formation of advanced glycation end products both contribute to the pathogenesis of hyperglycemic complications. AGEs also play a pivotal role in microvascular and macrovascular complications progression by receptors for advanced glycation end products (RAGE). RAGE activate by AGEs leads to up-regulation of transcriptional factor NF-kB and inflammatory genes. Around the globe, researchers are working in various approaches for therapeutical implications on controlling AGEs mediated disease complications. In this regard, one of the potential promising agents observed with a wide range of AGEs inhibition by food-derived natural products. Current biotechnological tools have been turned to natural products or phytochemicals to manufacture the molecules without compromising their functionality. Metabolic engineering and bioinformatics perspectives have recently enabled the generation of a few potent metabolites with anti-diabetic activity. As the primary focus, this review article will also discuss multidisciplinary approaches that emphasize current advances in anti-diabetic therapeutic action and future perspectives of natural products.